Filsafat Ekonomi Syariah Sebagai Landasan Sistem Ekonomi Syariah Bagi Pendidikan Umat Islam - Lestari, Indri Wahyu; N, Laili Irfatun; Albab, Ulil (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The Islamic economic philosophy is based on the interconnectedness of God, Man (Cosmic), and Nature (Cosmos), and is directed towards financial tasks such as economic principles, consumption, production, sales, and economic development. In Indonesia, the development of Islamic economics is influenced by internal and external factors. The key principles of Islamic economics in Indonesia are Tawhid, Maslahah, and Fair, which emphasize the relationship between humans and God, and humans and nature based on the principles of sharia. The country has also developed a masterplan for Islamic economic development, focusing on areas such as strengthening the halal value chain, the Islamic financial sector, and micro, small, and medium enterprises